Techniques for mandibular block anaesthesia - the practice of Nigerian dentists - O. A. Akadiri; A. A. Olusanya (Nigerian Dental Journal)
Objective: To assess the knowledge and practices of Nigerian dentists in the use of alternative techniques for inferior alveolar nerve block.